KARAKTERISASI SIMPLISIA DAN EKSTRAK DAUN BANDOTAN (Ageratum conyzoides L) SEBAGAI KANDIDAT OBAT KARIES GIGI - Ika Ayu Mentari; Wirnawati Wirnawati; Maulina Rahmawati Putri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Bandotan leaves (Ageratum conyzoides L) has an activity to inhibit the growth of Streptococus mutans bacteria cause dental caries. This Research was designed to establish quality and safety standards for simplicia and Bandotan leaves extracts. This research is non-experimental, which includes sampling, determination, making simplicia, and extraction. Characterization tests including organoleptic, macroscopic, microscopic, phytochemicals screening using TLC, determination of soluble water content, soluble ethanol content, total ash content, water soluble in ash content, acid insoluble in ash content and decrease drying. Organoleptic characteristics of simplicia test showed dark green, has bitter taste and aromatic odor typical of bandotan. The extract showed blackish green, aromatic aroma typical of bandotan and has very bitter taste. Phytochemical screening showed that bandotan leaf extract contains alkaloids, steroids, flavonoids. Microscopic of Simplicia showed hair covering, upper and lower epidermis, corrugated walls with anomistic type stomata, mesophyll covering palisade tissue. The percentage simplicia and extract of soluble water are 2% and 2,4 %. Percentage soluble ethanol are 12,9% and 9,5%. Percentage of total ash content 25,5% and 51%. Percentage water soluble in ash content are 10% and 7,35%. Percentage acid insoluble in ash content are 9,7 % and 2,5%. Percentage decrease drying are 11% and 75%.